2006
DOI: 10.2353/ajpath.2006.050137
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic Cardiomyocyte Death in Cardiomyopathic Hamsters and Its Prevention by Granulocyte Colony-Stimulating Factor

Abstract: In UM-X7.1 hamster model of human dilated cardiomyopathy, heart failure progressively develops and causes 50% mortality by 30 weeks of age. Through ultrastructural analysis, we found that many cardiomyocytes of this model contain typical autophagic vacuoles including degraded mitochondria, glycogen granules, and myelin-like figures. In addition, ubiquitin, cathepsin D, and Rab7 were overexpressed as determined by immunoassays. Importantly, most cardiomyocytes with leaky plasma membranes were positive for cathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 52 publications
1
80
0
Order By: Relevance
“…Cardiomyocytes obtained from UM-7.1 hamsters, which is the model of human dilated cardiomyopathy, contain typical autophagic vacuoles, including degraded mitochondria, glycogen granules and myelin-like figures. 43 In diphtheria toxin receptor transgenic mice, degenerated cardiomyocytes showing characteristics of autophagy have also been observed. 44 However, the question remains as to whether autophagy is a sign of failed cardiomyocyte repair or is a suicide pathway for the failing cardiomyocytes.…”
Section: Autophagy In Heart Failurementioning
confidence: 99%
“…Cardiomyocytes obtained from UM-7.1 hamsters, which is the model of human dilated cardiomyopathy, contain typical autophagic vacuoles, including degraded mitochondria, glycogen granules and myelin-like figures. 43 In diphtheria toxin receptor transgenic mice, degenerated cardiomyocytes showing characteristics of autophagy have also been observed. 44 However, the question remains as to whether autophagy is a sign of failed cardiomyocyte repair or is a suicide pathway for the failing cardiomyocytes.…”
Section: Autophagy In Heart Failurementioning
confidence: 99%
“…Many studies have demonstrated that autophagy is upregulated in the heart in response to stress such as ischemia/reperfusion [4,[8][9][10][11][12]. Increased numbers of autophagosomes are a prominent feature in many cardiovascular diseases such as cardiac hypertrophy and heart failure [13][14][15][16][17][18]. However, the functional role of the enhanced autophagy in the diseased heart is unclear and studies have yielded conflicting results regarding the role of autophagy in the heart.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Among these, activation of autophagic mechanisms has been detected in models of short-term nutrient deprivation, 15,19,20 chronic ischemia, 21 ischemia-reperfusion injury, 13,22 genetic cardiomyopathy, 23 and diphtheria toxin-induced injury. 24 Evidence of autophagic activity has been reported in patients with heart disease.…”
Section: Autophagy In Other Forms Of Heart Diseasementioning
confidence: 99%